2017
DOI: 10.1155/2017/3519158
|View full text |Cite
|
Sign up to set email alerts
|

XBP1-Mediated BiP/GRP78 Upregulation Copes with Oxidative Stress in Mosquito Cells during Dengue 2 Virus Infection

Abstract: Dengue viruses (DENVs) cause dengue fever which is an important mosquito-borne disease in tropical areas. Generally, DENV does not cause cellular damage in mosquito cells. However, alterations in cytosolic calcium ions ([Ca2+]cyt) and the mitochondrial membrane potential (MMP), as well as accumulated reactive oxygen species (ROS), including superoxide anions (O2∙−) and hydrogen peroxide (H2O2), can be detected in C6/36 cells with DENV2 infection. Evident upregulation of BiP/GRP78 also appeared at 24 h postinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…2000 ). Previous studies have demonstrated that during DENV infection the concentration of calcium ions rises in the cytoplasm ( Chen et al. 2017 ) as levels are simultaneously depleted in the ER ( Dionicio et al.…”
Section: Discussionmentioning
confidence: 99%
“…2000 ). Previous studies have demonstrated that during DENV infection the concentration of calcium ions rises in the cytoplasm ( Chen et al. 2017 ) as levels are simultaneously depleted in the ER ( Dionicio et al.…”
Section: Discussionmentioning
confidence: 99%
“…The UPR as mentioned above is caused by the accumulation of unfolded or misfolded proteins in the ER; which actually resulted in changes in X-box binding protein 1 (XBP1) and splicing activity [ 41 ]. The UPR generally leads to activation of three signaling pathways including PERK, IRE1 and ATF6 [ 5 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this contrasts with most other viral infections, which induce the upregulation of GRP78. [53][54][55] Recent studies have shown that some viruses manipulate the host UPR to maintain an environment favorable for persistent infection. For example, hepatitis C virus and cytomegalovirus have been reported to suppress the IRE1-XBP1 pathway of the UPR, 56,57 which was assumed to contribute to persistent infection of the virus in the cells.…”
Section: Discussionmentioning
confidence: 99%